Analysis of Amino Acids Levels of Freeze-dried Termite Queen Macrotermes gilvus Hagen: An Advanced Study - Yohannes Alen; Lakmi Nurul Suci; Orindia Suarmin; Harrizul Rivai (Recent Research Advances in Biology Vol. 7, 2021)
Objective: Termites (Macrotermes gilvus Hagen) are the social insects with colonies divided into ‘castes’ that include workers, soldiers, winged adults, a queen and a king. Queen of termites were analyzed for amino acid content. Methods: Amino acid analyses were carried out on the part reproductive termites to determine the nutrient composition. The queen termites were collected from palm plantation, Taluak Kuantan, Riau, Indonesia. They were opened from nest, freeze-dried to fine powder. Amino acids were determined using ultra pressure liquid chromatography (UPLC). Results: Freeze-dried termites queen showed that crude protein contain the essential amino acid. The highest content of amino acid was lysine, while the least content of amino acid was tryptophan. Conclusion: The queen of termites was the nutrient-rich insects that can supply adequate quantities of the various amino acids for pharmaceutical nutrient. The study confirms the fact that termites are indeed a good source of protein and amino acids.